Do Distance Education students owned their learning? Students’ perceptions of parenting styles and sex role ideologies. - Amoah, Samuel Asare (Advances in Social Sciences Research Journal, 2019)
Samuel Asare Amoah1, Francis Owusu-Mensah2, Abena Gyamera3 Gideon Mensah, Ankama4, Psychology and Education, Department, University of Education, Winneba asareamoahy@yahoo.com Institute of Distance and e-learning, University of Education, Winneba francisowusumensah@gmail.com Psychology and Education, Department, University of Education, Winneba Municipal Education Office, Ghana Education Service, Koforidua abenagyamera@yahoo.co.uk ABSTRACT Students have different ideologies about what they consider appropriate and inappropriate when it comes to learning. In view of this the study sought to find out if DE students own their learning regarding parenting styles and sex role ideologies. Correlational research design was employed in this study. Stratified and simple random sampling techniques were used to select 300 participants from a population of 1480. Using an adopted instruments the Pearson-Product Moment Correlation was used to establish association between parenting styles and sex role ideology and regression was used to ascertain the predictions of the variables. It was found that parenting styles do not contribute to sex role ideologies of the participants to foster learning. However, individuals with authoritative parenting style were more likely to form more modern sex role ideology which influences their learning episode, and individuals with authoritarian parenting style were more likely to have more traditional sex role ideology. The study recommends that since parenting styles relates with sex role ideology DE students need to be guided on how they learn through guidance and counselling to develop the best ideology to learning. Again cultural sentiment need to guide DE students who come from varied cultural settings. Key words: Parenting Styles, Sex role ideology, Distance Education students